Covid-19: UMP activates virtual classes - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
KUANTAN: Universiti Malaysia Pahang (UMP) is the latest higher learning institution in the country to activate e-learning for its students in a move to curb the spread of Covid-19.